The racial Muslim: when racism quashes religious freedom - Aziz, Sahar (De Gruyter eBook-Paket Rechtswissenschaften, 2022)
Foreword / by John Esposito -- Introduction -- When American racism quashes religious freedom -- The color of religion -- Racialization of Jews, Catholics, and Mormons in the twentieth century -- From Protestant to Judeo-Christian : the expansion of American whiteness -- Social construction of the racial Muslim -- American orientalism and the Arab terrorist trope -- Fighting terrorism, not religion -- Officiating Islamophobia -- Criminalizing Muslim identity -- The future of the racial Muslim and religious freedom in America -- Conclusion.